Pharmacological cognitive enhancement—how neuroscientific research could advance ethical debate - Maslen, Hannah; Faulmüller, Nadira; Savulescu, Julian (Frontiers in Systems Neuroscience, 2014)
There are numerous ways people can improve their cognitive capacities: good nutrition and regular exercise can produce long-term improvements across many cognitive domains, whilst commonplace stimulants such as coffee temporarily boost levels of alertness and concentration. Effects like these have been well-documented in the medical literature and they raise few (if any) ethical issues. More recently, however, clinical research has shown that the off-label use of some pharmaceuticals can, under certain conditions, have modest cognition-improving effects. Substances such as methylphenidate and modafinil can improve capacities such as working memory and concentration in some healthy individuals. Unlike their more mundane predecessors, these methods of ‘cognitive enhancement’ are thought to raise a multitude of ethical issues. This paper presents the six principal ethical issues raised in relation to pharmacological cognitive enhancers (PCEs) – issues such as whether: (1) the medical safety-profile of PCEs justifies restricting or permitting their elective or required use; (2) the enhanced mind can be an ‘authentic’ mind; (3) individuals might be coerced into using PCEs; (4), there is a meaningful distinction to be made between the treatment versus enhancement effect of the same PCE; (5) unequal access to PCEs would have implications for distributive justice; and (6) PCE use constitutes cheating in competitive contexts. In reviewing the six principal issues, the paper discusses how future neuroscientific research might help advance the ethical debate. In particular, the paper presents new arguments about the contribution neuroscience could make to debates about justice, fairness and cheating, ultimately concluding that neuroscientific research into ‘personalised enhancement’ will be essential if policy is to be truly informed and ethical. We propose an ‘ethical agenda’ for neuroscientific research into PCEs.